2004
DOI: 10.1111/j.1365-294x.2004.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating system of the Eurasian badger,Meles meles, in a high density population

Abstract: Badgers are facultatively social, forming large groups at high density. Group-living appears to have high reproductive costs for females, and may lead to increased levels of inbreeding. The extent of female competition for reproduction has been estimated from field data, but knowledge of male reproductive success and the extent of extra-group paternity remains limited. Combining field data with genetic data (16 microsatellite loci), we studied the mating system of 10 badger social groups across 14 years in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 63 publications
8
104
3
Order By: Relevance
“…Territorial behaviour in Woodchester Park was very pronounced, with nonoverlapping group ranges and intensive territorial markings (Cheeseman et al, 1981). The average territory size in this locality has been reported as 0.26 km 2 (Cheeseman et al, 1981) and the average distance between main setts as 0.57 km (Carpenter et al, 2005).…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Territorial behaviour in Woodchester Park was very pronounced, with nonoverlapping group ranges and intensive territorial markings (Cheeseman et al, 1981). The average territory size in this locality has been reported as 0.26 km 2 (Cheeseman et al, 1981) and the average distance between main setts as 0.57 km (Carpenter et al, 2005).…”
Section: Methodsmentioning
confidence: 96%
“…A large number of loci deviated from HardyWeinberg genotypic proportions in the UK population. However, the 16 loci used in the present study were developed from individuals captured in Woodchester Park (Carpenter et al, 2003), in which no systematic heterozygote deficiencies were observed when performing analyses on adults and cubs separately (Carpenter et al, 2005). The deviations from Hardy-Weinberg proportions are therefore not an intrinsic characteristic of these loci (see also Frantz et al, 2004;Pope et al, 2006), but very likely the result of the strong spatial autocorrelation pattern observed in the UK study area (Frantz et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They note that a large proportion of the paternities are inferred to be from unsampled males from outside of the study area and conclude that promiscuity is a strategy to minimize inbreeding. Carpenter et al (2005) also made use of a molecular marker-based pedigree in their recent study of the Eurasian badger Meles meles mating system. They also found that badgers exhibit high levels of extra-group matings, attributed to inbreeding avoidance, and suggest that the tactic could help social cohesion by reducing the cost of philopatry.…”
Section: Uses In Animal Conservation Studiesmentioning
confidence: 99%